THE USE OF TITRIMETRIC, NELSON SOMOGYI AND HPLC METHODS FOR THE ANALYSIS OF CASHEW APPLE JUICE FERMENTATION BROTHS - Julia Kantasubrata; A. T. Karossi; A. S. Pramudi (Jurnal Kimia Terapan Indonesia, 1993)
In cashew apple juice fermentation to produce wine and vinegar, analysis of organic acids and sugars in fermentation broths is very important, due to the fact that optimum conditions of fermentation could only be established from results obtained on monitoring the concentrations of those components during the fermentation process. Analysis of organic acids by tiirimetric method and analysis of sugars by Nelson-Somogyi method only give a total amount of acids and sugars. HPLC is one of the promising method for determining the acids/sugars individually, although this method needs costly facilities such as columns and so/vents. In this work, organic acids were separated by HPLC on a u-Bondapak C1B column using aqueous solution of 2% NH4H2O4 as the mobile phase, while sugars were separated on silica-based column using an eluent containing a polyamine reagent. In this investigation the results of determination of organic acids by titrimetric method and those of sugars by Nelson-Somogyi method were compared respectively with the results of individual organic acids and sugars obtained from the HPLC methods. It was found that for organic acids, results of the determination using the titrlmetric method is correlated linearly with the results of acetic acid obtained by the HPLC methods. The same results were obtained for total and reducing sugars determination by the Nelson-Somogyi and individual sugar by the HPLC methods. The regression equation obtained for each of the organic acids and sugars can be used for the estimation of each of the respective components present in the cashew apple juice fermentation broths based on the results obtained from both titrimetric and Nelson-Somogyi methods. For routine monitoring of large number of fermentation broth samples, the proposed method was found to be a better alternative to the more castly HPLC method.